Sistem Monitoring Berbasis Web Untuk Stasiun Cuaca Dengan Metode Extreme Programming (Studi Kasus: PT. Meteo Nusantara Instrumen) - Suparli (CV. Multi Kreasi Media, 2023)
PT Meteo Nusantara Instrumen (MNI) is a company engaged in meteorological instrumentation, agroclimatology, water resources and air quality both as a distributor and manufacture of tools. MNI has approximately 50 clients spread throughout Indonesia, where each client has at least 1 weather station tool, for data collection from weather stations is done manually, and clients are burdened by routine activities that are carried out repeatedly and inefficiently even though ideally handled by a technology system. Another problem is that the tools installed by the client are usually placed in places that are difficult to access. This study aims to create a Web-Based Monitoring System for Weather Stations With the Extreme Programing Method that can be used by clients for data retrieval and monitoring the status of installed tools. The method used is Extreme Programing which focuses on simplifying the SDLC (System Development Life Cycle) model so that the development process is faster in realization. Starting from digging up information about the system picture through the Unstructured Interview elisitation technique, regarding what the system needs to do. Furthermore, the researcher makes an application design and creates program code in a simple module according to the needs of the company. With this system, the client no longer needs to take data manually by visiting the location of the installed tool, the client only needs to open the website to log in and can immediately monitor and download the data needed. The results of the research that has been carried out have succeeded in creating a Web-Based Monitoring System for Weather Stations that can be used for monitoring weather station tools that previously used manual methods. With this system, PT Meteo Nusantara Instrumen clients can eliminate the large effort and costs incurred only for retrieving data from weather stations. To integrate tools that were not previously telemetry, users can add modules available in PT. Meteo Nusantara Instrumen.